Parasphaerolaimus magdolnae sp. n. (Nematoda, Sphaerolaimidae) with intra-uterine development of its offspring from a Brazilian estuarine system - Cavalcanti, Mariana Da Fonseca; Venekey, Virag (Zootaxa, 2017)
One new species of Parasphaerolaimus is described from a Brazilian estuarine system with intra-uterine development of its offspring. Parasphaerolaimus magdolnae sp. n. is distinguished from other species of the genus by the presence of only one anterior testis, spicules morphology and size and a gubernaculum without dorsal apophysis. The cuticle of the new species is striated and the position of the vulva is far posterior on the body, almost reaching the anus. The taxonomy of Parasphaerolaimus was also re-examined and two other species were transferred from Sphaerolaimus to Parasphaerolaimus after the last revision: P. pentasetus (Pastor de Ward, 1984) comb. n. and P. striatus (Allgén, 1935) comb. n. An updated identification key for all valid species of Parasphaerolaimus is included.